UJI AKTIVITAS SAPONIN DARI EKSTRAK GETAH BIDURI (Calotropis gigantea) SEBAGAI LARVASIDA NYAMUK Aedes aegypti - admin (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2016)
Calotropis gigantea or biduri, a wild plant that is found in season long dry areas such as the slopes of the low and sandy beaches, but its existence is not fully understood by the people around. Biduri sap containing saponins and protease enzymes are thought to be used as larvicides. Saponin is a chemical compound found in many kinds of plants and herbs along with other secondary substance acts as a defense against attack. The purpose of this study was to determine the larvicidal activity of a saponin extract containing latex biduri (Calotropis gigantea) against larvae of Aedes aegypti. This study, an experimental laboratory research design the post-test only controlled group design. This study, conducted experiments on larvae of Aedes aegypti by treatment with the extract concentration Biduri different. The sap extraction biduri (Calotropis gigantea) using ethanol, and then partitioned with a mixture of water : ethanol (1: 1). The extract used is a concentration of 0; 0,125% ; 0,250% ; 0,500% and 0,600% givento the larvae of Aedes aegypti. The results of the study percentage of larval mortality 24 hours after treatment was 0% in controls; 27% in the extract sap biduri 0,125%; 50% on the extract sap biduri 0,250%; 93% on the extract of 0,500%, whereas in the group biduri sap extract 0,600% the number of larvae mortality was 100%. Results obtained significant difference between each treatment group (p <0,05) except between groups of 0,500% and 0,600% (p> 0.05) were not significant. Probit analysis results indicate that the LC50 values ​​194,984 ppm LC99 while the concentration of 831,76 ppm. Conclusion extract sap biduri (Calotropis gigantea) has larvicidal effect against larvae of Aedes aegypti in the category of toxic with LC50 <1000 ppm is 194.984 ppm while larval mortality of 99%(LC99 ) at a concentration of 831,76 ppm.